Isolation and characterization of novel Lactobacillus spp. with promising gastro-intestinal survival and adhesion properties - Klopper, Kyle Brent (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.